2011
DOI: 10.1371/journal.pone.0026358
|View full text |Cite
|
Sign up to set email alerts
|

Benefit from B-Lymphocyte Depletion Using the Anti-CD20 Antibody Rituximab in Chronic Fatigue Syndrome. A Double-Blind and Placebo-Controlled Study

Abstract: BackgroundChronic fatigue syndrome (CFS) is a disease of unknown aetiology. Major CFS symptom relief during cancer chemotherapy in a patient with synchronous CFS and lymphoma spurred a pilot study of B-lymphocyte depletion using the anti-CD20 antibody Rituximab, which demonstrated significant clinical response in three CFS patients.Methods and FindingsIn this double-blind, placebo-controlled phase II study (NCT00848692), 30 CFS patients were randomised to either Rituximab 500 mg/m2 or saline, given twice two w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
164
2
13

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 174 publications
(189 citation statements)
references
References 28 publications
10
164
2
13
Order By: Relevance
“…Findings in this study provide further evidence that ME/CFS likely involves a systemic inflammatory process (17). These findings also support biological plausibility for the propensity of these patients to experience several major and ongoing clinical manifestations, offer a mechanism for the disease's predilection to affect women and the increased risk for development of NHL, and support the suitability of exploring immunomodulation as a primary or adjuvant therapy (56,57). Future cytokine research in the peripheral blood of ME/CFS patients should embrace longitudinal designs and seek correlations with neuroradiology, neuroinflammation, and CSF studies.…”
Section: Discussionsupporting
confidence: 73%
“…Findings in this study provide further evidence that ME/CFS likely involves a systemic inflammatory process (17). These findings also support biological plausibility for the propensity of these patients to experience several major and ongoing clinical manifestations, offer a mechanism for the disease's predilection to affect women and the increased risk for development of NHL, and support the suitability of exploring immunomodulation as a primary or adjuvant therapy (56,57). Future cytokine research in the peripheral blood of ME/CFS patients should embrace longitudinal designs and seek correlations with neuroradiology, neuroinflammation, and CSF studies.…”
Section: Discussionsupporting
confidence: 73%
“…Our previous findings in interventional clinical trials evaluating B lymphocyte depletion therapy, using the monoclonal anti-CD20 antibody rituximab, suggest that ME/CFS in a subgroup of patients could be a variant of an autoimmune disease (38)(39)(40), possibly involving antibodies. Future research should address the metabolic effects in ME/CFS reported in the present study in the context of a possible immunological mechanism.…”
Section: Discussionmentioning
confidence: 93%
“…A 67% improvement was seen in the self-reported fatigue scores of those who received rituximab, and a 13% improvement was seen in those who received placebo. There were no differences in B cell levels between patients in the rituximab group who achieved a response compared with those who did not (39).…”
Section: Reviewmentioning
confidence: 77%